Efficacy of Sodium Valproate in the Treatment of Photosensitive Epilepsy (PSE) and the Probable Reasons for the Persistence of Occipital Spikes - Ebere C. Anyanwu; John E. Ehiri; Andrew W. Campbell (The Scientific World Journal)
Intermittent photic stimulation (IPS) in patients with photosensitive epilepsy (PSE) leads to EEG abnormalities, which include generalized discharges with spike and wave activity. This paper investigates 33 PSE patients, 14 (42%) males and 19 (58%) females. The age range was between 8 and 45 years. After the treatment of the patients with sodium valproate (VPA), the EEG examinations showed that the generalized discharges disappeared, while the occipital spikes persisted. The mechanism of action of VPA was re-evaluated in order to ascertain whether or not the persistent occipital was due to a failure in inhibitory postsynaptic potential (IPSP). It was concluded that the possible causes of VPA's inefficacy in abolishing occipital spikes in PSE was not necessarily due to a failure in IPSP, but rather it could be due to a time-dependent failure of certain cells of the visual system to respond positively to the VPA's modulatory activity, probably involving the ionic channels, neurotransmitters, and the second messenger systems. The relationship between occipital spikes and visual evoked response is discussed. The extent to which metabolic processes and neurotransmitters are involved is also evaluated.